“Evaluación multilocal de la eficiencia y adaptación de 4 híbridos de maíz amarillo duro introducidos del brasil al Huallaga central” - Torres Flores, Angel Segundo (2004)
The present titled project "Evaluation Multilocal of the Efficiency and Hybrid Adaptation of 4 of lntroduced Hard Yellow Corn of the Brazil to the Central Huallaga"; he/she has as objective, to determine the hybrid agronomic value of 4 of introduced hard yellow corn of the Brazil, in the sectors of Buenos Aires, Huinge, and Puerto Rico; and to determine the economic analysis of the studied treatments. The investigation work was carried out in the sectors of Buenos Aires, Huinge and Puerto Rico. Each one dista of the highway Fernando Belaunde Terry: Buenos Aires to 2 Km to the south right margin. Huinge to 1 Km to the south left margin, Puerto Rico to 30 Km to the south left margin. The experiment was carried out at random under a design of complete blocks with 9 treatments ar hybrid and 3 repetitions, the hybrid employees were BRS 1010, NK STAR, MASTER, BRS 1001, AG 5572, BRS 3151, XB 8010, C-701 ANO BRS 2223. The results hurtled that the biggest plant heights and to the ear they registered in the town of Huinge with the hybrid MASTER. The hybrid C-701 showed to be more resistant to the one it flattens of root and it plants because it didn't register any flattened plant; on the other hand the hybrid BRS 2223 registered the biggest quantity in plant flattened in comparison with the other treatments in study. The hybrid BRS 2223 demonstrated to be more precocious to 50 floración% in the three towns. Likewise the hybrid MASTER threw bigger yields and utilities in the towns Buenos Aires y Puerto rico with 11,06; 13,06 t/ha and S /. 2013,59; S /. 2 263,25 respectively.